Electromagnetic control and heat transfer enhancement in exothermic reactions experiencing current density: The study preventing thermal explosions in reactive flow - Gasmi Hatem; Akindele Akintayo Oladimeji; Obalalu Adebowale Martins; Usman Abdulazeez Adebayo; Khan Umair; Yilmaz Yalcin; Taiwo Musilimu; Hussain Syed Modassir; Nizampatnam Neelima (Applied Rheology)
Thermal explosions in reactive flows present an important risk to industrial engineering systems, where uncontrolled exothermic reactions can compromise safety and operational integrity. This study investigates the theoretical solutions related to thermal runaway and heat transport in a branch-chain bifurcation scenario influenced by hydromagnetic Powell–Eyring fluid flow. By incorporating factors such as current density and variable properties, we aim to enhance the safety, reliability, and efficiency of industrial operations, thus contributing to the development of more robust and sustainable systems. Notably, the fluid is characterized by active exothermic behavior under bimolecular kinetics, challenging traditional material assumptions. Utilizing a spectral collocation scheme alongside exact solutions, we derive critical parameters, including flow velocity, current density, bifurcation branch-chain criticality, entropy generation rate, and heat propagation. Our findings reveal that increased electric field conductivity significantly enhances the current density along the channel walls, driven by the combined effects of the Frank–Kamenetskii term and electric field loading. Furthermore, understanding thermal explosions and branched-chain reactions is essential for preventing engine failures, underscoring the practical implications of this research in industrial contexts.